(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
ABSTRACT Objective: To determine the effectiveness of facet joint steroid injection in combination with lignocaine in chronic low back ache by measuring the reduction of pain intensity. Methods: This Descriptive study was conducted at the Department of Orthopedic and Trauma Khyber Teaching Hospital Peshawar from 1/02/2018 to 31/07/2018.All patients with chronic low back ach(for three months or more) meeting the inclusion criteria were included. Pre pain was assessed using visual analog scale (VAS). Under image intensifier each facet joint was be infiltrated with a mixture containing 10 mg of steroid and 2 ml of 1% lidocaine. Follow ups were done at six weeks time and improvement was measured using the same grading system(VAS) to confirm the effectiveness of the procedure. Treatment was considered effective if the patient score below 4 on VAS after treatment with facet joint steroid injection. Results: In our study 145 patients with chronic low back ache were analyzed. The mean age was 56 years with SD ± 22.91. The percentage of male patients were 52% while 46% were female. Mean duration of low back ache was 8 month with SD ± 3.37. Facet joint steroid injection was efficacious in 67% patients and was ineffective in 33% patients. Conclusion: Facet joint steroid injection in combination with lignocaine is effective in reducing chronic backache and discomfort to the patients.